Continuous Synthesis of Zn2Al-CO3 Layered Double Hydroxides for the Adsorption of Reactive Dyes from Water. Issue 3 (June 2019) - Clark, Ian; Smith, Jacob; Gomes, Rachel L.; Lester, Edward
Highlights: Calcined LDH (MMO) exhibits greater adsorption capacity than activated carbons. Evidence that dyes intercalate into interlayer region of regenerated LDH. RO16 undergoes higher adsorption than RB5 due to dye structure. Regeneration mechanism elucidated showing a 'memory mechanism'. Abstract: A novel pilot scale approach to continuous synthesis of layered double hydroxides (LDHs) was used to produce Zn2 Al-CO3 . The Zn2 Al-CO3 was calcined and used in the adsorption of Reactive Black 5 (RB5) and Reactive Orange 16 (RO16) from water. The specific surface area of the LDH was 50.1 m 2  g -1, while the surface area of the calcined LDH (MMO) was 57.8 m 2  g -1 . X-ray diffraction indicated complete breakdown of the LDH at 500 °C for 4 hours, with amorphous Al2 O3 or AlOOH alongside ZnO. Reaction variables in the adsorption system; temperature, adsorbent dose, pH, initial concentration and the effect of competing anions were investigated across four temperatures from 10 °C to 40 °C. Maximum adsorption capacity calculated from the Langmuir isotherm was 895 mg g -1 and 589 mg g -1 at 20 °C, for RB5 and RO16, respectively. Intercalation of dye molecules was the main mode of adsorption, as indicated by shifts in ( 003 ) reflection from 11.5° to 4.5° and 3.2° for RB5 and RO16 respectively. Adsorption was best modelled by the pseudo 2 nd order kinetic model. The intra-particle diffusion model indicated multiple stages of adsorption; surface adsorption occurs initially, followed by, intra-particle diffusion of dye molecules into the interlayer region. Regeneration through calcination resulted in an adsorption equal to 99 ± 2%.